JORDANIAN FOREIGN POLICY TOWARDS THE COUNTRIES OF THE GULF COOPERATION COUNCIL (1999-2019) - Saddoon N. Al-Majali (International Journal of Innovative Technologies in Social Science, 2019)
The study aimed to research the Jordanian foreign policy towards the Gulf Cooperation Council states during the period 1999-2019, as this period is an extension of the previous stages, as during which Jordanian relations with the countries of the Gulf Cooperation Council were affected as a result of the second Gulf crisis 1990, and the events of September 2001, and what followed in light of the war on Iraq and its occupation by the United States of America, where the United States emerged as a unipolar force that dominates the world. The study showed that Jordanian foreign policy towards the Gulf Cooperation Council countries was affected by regional and international changes, as relations between Jordan and the countries of the Gulf Cooperation Council were characterized by apathy and approached isolation as a result of Iraq’s occupation of Kuwait, but Jordanian relations with the Gulf Cooperation Council countries improved, as a result of The multiple visits made by King Abdullah II after he assumed power in 1999, to the countries of the Gulf Cooperation Council, as Jordan’s geopolitical position contributes to enhancing security and stability for the countries of the Council in exchange for Israeli expansionist ambitions, because Jordan looks at its security cooperation with the Gulf Cooperation Council (GCC) in the framework of the imperatives of mutual security, which posed this perspective as one of the dimensions in the Gulf of Jordan’s foreign policy, which has not changed even in periods of Arab division, or during the boycott Cooperation Council (GCC) to Jordan.